The Reversal Effect of Sigma-1 Receptor (S1R) Agonist, SA4503, on Atrial Fibrillation After Depression and Its Underlying Mechanism - Liu, Xin; Qu, Chuan; Shi, Shaobo; Ye, Tianxin; Wang, Linglin; Liu, Steven; Zhang, Cui; Liang, Jinjun; Hu, Dan; Yang, Bo (Frontiers in Physiology, 2019)
Aims: Sigma-1 (σ1) receptors have been investigated to play a protective role in both depression and cardiovascular disease. SA4503, known as a σ1 receptor agonist, regulates cardiac calcium and potassium channels in rat model of depression. However, it remains unknown whether SA4503 can alleviate myocardial inflammation nor conduction junctions in atrium after exposure to chronic mild stress. Methods and Results: Male Sprague Dawley rats received 28-day treatment with SA4503, or vehicle, simultaneously with chronic mild stress. Behavior measurements were assessed after the daily doses. Additionally, multielectrode array assessment, electrophysiological study, immunohistochemistry analysis, histological analysis, and Western blot analysis were performed. Depression rats’ hearts showed abnormal electrical activity including the disordered excitation propagation and the prolonged total activation time (TAT). In addition, electrically induced atrial arrhythmias (AAs) were facilitated by depression in isolated hearts. The increased incidence and duration of electrically induced AAs were associated with reduced conduction junctions and enhanced spatial heterogeneity. Importantly, depressed rat hearts showed greater expression of inflammatory factors (TGF- and IL-6), and lower expression of gap junction proteins (CX40 and CX43). Furthermore, SA4503, partially mitigated the above indices in the depression group (P  0.01 for all groups). Conclusions: These findings show effects of σ1R agonist SA4503 alleviates atrial myocardial inflammation and conduction junctions after chronic mild stress. SA4503 may be the promising pharmacological agent to treat depression related AAs by increasing conduction function, improving the expression of connexin 40 and 43, and reducing cardiac myocardial inflammation.